Analisis Dan Perancangan Sistem Informasi Pelayanan Nasabah Menggunakan Metode Queuing System (Studi Kasus: Bank Pembangunan Daerah Jambi Kantor Cabang Utama) - Eriadi, Rawiko; Mulyono, Herry (Jurnal Manajemen Sistem Informasi, 2020)
The phenomenon of waiting for queues often occurs in everyday life. this happens because of the need formore service delivery services. At the Jambi Regional Development Bank Main Branch, the queue systemis still manually manual. One of the processes found in the Jambi Branch Main Branch DevelopmentBank is that there can be a buildup of queues with long waiting lines. Often also occurs in understandingqueue numbers that are not arranged sequentially, so as to affect the long waiting for customers. For thisreason, in this study a relevant system was developed to provide information for customers and assistofficers in managing the queue. This queue system is built using the FCFS model and Microsoft VisualBasic 6.0.